# Find-the-value-of-n-so-that-a-n-1-b-n-1-a-n-b-n-may-become-the-G-M-between-a-and-b-

Question Number 3465 by Rasheed Soomro last updated on 13/Dec/15
$${Find}\:{the}\:{value}\:{of}\:{n}\:{so}\:{that} \\$$$$\:\:\:\:\:\:\:\:\:\:\frac{{a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} }{{a}^{{n}} +{b}^{{n}} } \\$$$${may}\:{become}\:{the}\:{G}.{M}.\:{between}\: \\$$$${a}\:\:{and}\:\:\:{b}. \\$$
Answered by prakash jain last updated on 13/Dec/15
$$\frac{{a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} }{{a}^{{n}} +{b}^{{n}} }=\sqrt{{ab}} \\$$$${a}/{b}={k}\Rightarrow{a}={kb} \\$$$$\frac{{k}^{{n}+\mathrm{1}} +\mathrm{1}}{{k}^{{n}} +\mathrm{1}}{b}={bk}^{\mathrm{1}/\mathrm{2}} \\$$$$\frac{{k}^{{n}+\mathrm{1}} +\mathrm{1}}{{k}^{{n}} +\mathrm{1}}={k}^{\mathrm{1}/\mathrm{2}} \\$$$$\frac{{k}^{\mathrm{2}{n}+\mathrm{2}} +\mathrm{1}+\mathrm{2}{k}^{{n}+\mathrm{1}} }{{k}^{\mathrm{2}{n}} +\mathrm{1}+\mathrm{2}{k}^{{n}} }={k} \\$$$${k}^{\mathrm{2}{n}+\mathrm{2}} +\mathrm{1}+\mathrm{2}{k}^{{n}+\mathrm{1}} ={k}^{\mathrm{2}{n}+\mathrm{1}} +{k}+\mathrm{2}{k}^{{n}+\mathrm{1}} \\$$$${k}^{\mathrm{2}{n}+\mathrm{2}} +\mathrm{1}={k}^{\mathrm{2}{n}+\mathrm{1}} +{k} \\$$$$\Rightarrow{n}=−\frac{\mathrm{1}}{\mathrm{2}} \\$$$$\\$$
Commented by prakash jain last updated on 13/Dec/15
$$\mathrm{Check} \\$$$$\frac{\sqrt{{a}}+\sqrt{{b}}}{\frac{\mathrm{1}}{\:\sqrt{{a}}}+\frac{\mathrm{1}}{\:\sqrt{{b}}}}=\frac{\sqrt{{a}}+\sqrt{{b}}}{\:\sqrt{{a}}+\sqrt{{b}}}×\sqrt{{ab}}=\sqrt{{ab}} \\$$
Answered by RasheedSindhi last updated on 14/Dec/15
$$\\$$$$\frac{{a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} }{{a}^{{n}} +{b}^{{n}} }=\sqrt{{ab}}={a}^{\frac{\mathrm{1}}{\mathrm{2}}} {b}^{\frac{\mathrm{1}}{\mathrm{2}}} \\$$$${a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} ={a}^{\frac{\mathrm{1}}{\mathrm{2}}} {b}^{\frac{\mathrm{1}}{\mathrm{2}}} \left({a}^{{n}} +{b}^{{n}} \right) \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:={a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} {b}^{\frac{\mathrm{1}}{\mathrm{2}}} +{a}^{\frac{\mathrm{1}}{\mathrm{2}}} {b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \\$$$$\:\:{a}^{{n}+\mathrm{1}} −{a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} {b}^{\frac{\mathrm{1}}{\mathrm{2}}} +{b}^{{n}+\mathrm{1}} −{a}^{\frac{\mathrm{1}}{\mathrm{2}}} {b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} =\mathrm{0} \\$$$${a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \left({a}^{\frac{\mathrm{1}}{\mathrm{2}}} −{b}^{\frac{\mathrm{1}}{\mathrm{2}}} \right)−{b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \left({a}^{\frac{\mathrm{1}}{\mathrm{2}}} −{b}^{\frac{\mathrm{1}}{\mathrm{2}}} \right)=\mathrm{0} \\$$$$\left({a}^{\frac{\mathrm{1}}{\mathrm{2}}} −{b}^{\frac{\mathrm{1}}{\mathrm{2}}} \right)\left({a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} −{b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \right)=\mathrm{0} \\$$$${a}^{\frac{\mathrm{1}}{\mathrm{2}}} −{b}^{\frac{\mathrm{1}}{\mathrm{2}}} =\mathrm{0}\mid\left({a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} −{b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \right)=\mathrm{0} \\$$$${a}^{\frac{\mathrm{1}}{\mathrm{2}}} ={b}^{\frac{\mathrm{1}}{\mathrm{2}}} \mid{a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} ={b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \\$$$${a}={b}\Rightarrow{n}\:{may}\:{be}\:{any}\:{number} \\$$$${a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} ={b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} \Rightarrow\frac{{a}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} }{{b}^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} }=\mathrm{1}\Rightarrow\left(\frac{{a}}{{b}}\right)^{{n}+\frac{\mathrm{1}}{\mathrm{2}}} =\left(\frac{{a}}{{b}}\right)^{\mathrm{0}} \\$$$$\:\:\:\:\:\:\Rightarrow{n}+\frac{\mathrm{1}}{\mathrm{2}}=\mathrm{0}\Rightarrow{n}=−\:\frac{\mathrm{1}}{\mathrm{2}} \\$$